Another new species of flightless Rail (Aves: Rallidae: Rallus) from Abaco, The Bahamas - Takano, Oona M.; Steadman, David W. (Zootaxa, 2018)
We describe a late Pleistocene species of extinct rail, Rallus gracilipes n. sp., from Sawmill Sink blue hole on Abaco Island, Little Bahama Bank, The Bahamas. The only other extinct rail known from any Bahamian island is the smaller Rallus cyanocavi, also from late Pleistocene contexts at Sawmill Sink. No fossils of R. gracilipes or R. cyanocavi have been found in Holocene sites on Abaco; the loss of both of these species is likely to be due to changes in climate, habitat, and island area during the Pleistocene-Holocene Transition.